1974
DOI: 10.1042/bj1370319
|View full text |Cite
|
Sign up to set email alerts
|

A study of the reaction of protoporphyrin IX with human globin

Abstract: The present paper reports an investigation of the reaction of protoporphyrin IX with globin prepared from the HbA(0) component of human blood. The porphyringlobin produced is always heterogeneous; however, when globin is used immediately after preparation, its affinity for porphyrin is higher and the product less heterogeneous than when the globin has been frozen or freeze-dried. The affinity of globin for haemin is less affected by its history. With freshly prepared globin, reconstitution at room temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
(13 reference statements)
5
13
0
Order By: Relevance
“…They also suggest that the residues that lie in close proximity to the porphyrin ring are the first to be photodamaged (22). Light-induced dissociation of protoporphyrin from hemoglobin is supported by the studies of de Goeij et al (14) who showed that the amount of protoporphyrin not associated with hemoglobin increased after blood samples from patients with erythropoietic protoporphyria had been exposed to light.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…They also suggest that the residues that lie in close proximity to the porphyrin ring are the first to be photodamaged (22). Light-induced dissociation of protoporphyrin from hemoglobin is supported by the studies of de Goeij et al (14) who showed that the amount of protoporphyrin not associated with hemoglobin increased after blood samples from patients with erythropoietic protoporphyria had been exposed to light.…”
Section: Discussionsupporting
confidence: 64%
“…In erythropoietic protoporphyria Lamola et al (16) propose that protoporphyrin in the erythrocytes is bound to intersubunit places on hemoglobin, whereas van Steveninck et al (15) suggest that protoporphyrin is bound to heme binding sites on globin. In the presence of globin, however, protoporphyrin is bound on the heme binding sites (16,22). In the present experiments ( Fig.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The latter corresponded to the Soret maximium observed in the absorption spectra of these plrel)arations. The spectral characteristics agree exactly with those reported in the literature for similar preparations (13,(18)(19)(20).…”
Section: Introductionsupporting
confidence: 81%
“…It can interact with many proteins, [23][24][25] and serves as a photodynamic agent in cancer therapy. 26,27 PPIX tends to aggregate into micelles in aqueous solution with low fluorescence, 28,29 but its fluorescence intensity is drastically increased when it binds to G-quadruplexes.…”
Section: Introductionmentioning
confidence: 99%